PROCESSING NIPAH LEAVES INTO DIETARY JELLY CANDY USING FERMENTATION TECHNOLOGY WITH FAMILY WELFARE DEVELOPMENT - Wahyuni, Nelly; Simamora, Cico Jhon Karunia; Jumiati, Jumiati; Pramulya, Muhammad; Utomo, Kiki Prio (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This service activity is aimed at optimizing the potential of Lactobacillus plantarum fermented palm leaves to become low-calorie diet jelly candy. This activity took place in Jeruju Besar Village, Kubu Raya, Pontianak, with PKK women. Local communities are expected to become entrepreneurs in order to improve family welfare. The results of the community service program, specifically in the aspect of applying appropriate science and technology for processing food products based on local potential, namely the nipa plant, are seen as very effective in building community independence. In terms of benefits, it is also quite substantial, namely increasing the added value of nipa leaves, raising people's awareness, knowledge, and skills in utilizing and processing nipa leaves into jelly candy.